Sustainability of animal origin food waste in Serbia. (September 2019) - Djekic, S; Tomasevic, I; Miloradovic, Z; Subić, J; Roljević, S; Djekic, I
Abstract: This research analysed attitudes related to food waste sustainability and estimated amounts of animal origin food waste and food packaging waste discarded in Serbia. The field survey covered 494 respondents from Belgrade, Serbia. Results present their degree of agreement with nine selected food waste sustainability statements and their reported quantities of discarded animal origin food waste and food packaging waste. Our study showed respondents have a higher rate of agreement related to the negative social and environmental dimensions of food waste, while they have no opinions associated with the economic dimensions. Regarding animal origin food waste quantities, it is estimated that households dispose around 200 g of waste every week (11.3 kg per year) and slightly under 30 different pieces of food packaging. On an annual basis, 7, 234 tons of CO2 emissions can be associated with animal origin food waste and 706.4 tons with food packaging waste in Serbia.